Acute compartment syndrome with dorsalis pedis artery rupture after an acute ankle inversion trauma - Gregorio Villarreal Villarreal; Omar Ituriel Vela Goñi; Gerardo Lozano Balderas; José Fernando de la Garza Salazar; Adriana Hernandez Lopez (Journal of the Foot & Ankle)
Acute compartment syndrome in lower limbs is commonly seen in fractures, crash injuries, vascular impairment, and rarely due to ankle sprain. We report a case of a 16-year-old male who was admitted to the emergency room after a traumatic lateral ankle inversion. Significant swelling and moderate pain were present at admission. Plain radiographs showed no bone abnormality. After 60 minutes, the classic signs and symptoms of acute compartment syndrome began, with no response to painkillers. Doppler ultrasound revealed arteries occlusion distal to the superior portion of the extensors retinaculum of the ankle. Anterior foot and ankle fasciotomy were performed, with an angiography revealing a dorsalis pedis artery rupture; both ends were ligated intraoperatively. Postoperative flow was observed through the local collateral system. Level of Evidence IV; Therapeutic Studies; Case Report